STRATEGI PROMOSI MELALUI SOCIAL MEDIA NETWORKING - I Made Bayu Pranata (Universitas Pendidikan Nasional, 2013)
As the development of technology which leads the world to globalization era,resulting the change in various fields. Competitive in business among companies in domesticand international market is getting strict, demanding all companies to more aggressive andbrave in decision making as well as applying companies promotion strategy so that theybecome more superior than their competitor. Information technology, particularly internet,influences marketing world strictly, even utilization of internet for marketing is considered asa trend setter. Facebook Marketing is one of the marketing ways through internet by utilizingthe functions available in social networking, Facebook and Twitter.Promotion strategy is a companies’ activity in influencing costumers for buying theproduct offered. Promotion through social media networking is the companies’ obligation,particularly BNI, as a media in introducing its product. Therefore, the problem raised in thisresearch is how about the applying of BNI promotion strategy through social medianetworking, Face book and Twitter.Keywords: Promotion Strategy, Social Media Networking